1997
DOI: 10.1007/bf03039187
|View full text |Cite
|
Sign up to set email alerts
|

The significance of a supraclavicular node metastasis in patients with breast cancer

Abstract: The prognosis is rather dismal as supraclavicular nodes are mostly the prelude to new metastases. Supraclavicular nodes can well be treated but the treatment does not influence survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
(57 reference statements)
0
18
0
1
Order By: Relevance
“…Die Vorteile der Axilladissektion sind eine ausgezeichnete lokale Tumorkontrolle und eine eventuelle Hilfe zur Indikationsstellung fur eine Systemtherapie [32,40,43], da ein Befall der axill~iren Lymphknoten als wichtigster Prognosefaktor gilt [22,24,28,36,69,82,113,124]. Der Wert der Axilladissektion for das GesamtUberleben wird allerdings noch diskutiert, die dazu bekannten Daten sind begrenzt und unbefriedigend.…”
Section: Stellenwert Der Axilladissektionunclassified
“…Die Vorteile der Axilladissektion sind eine ausgezeichnete lokale Tumorkontrolle und eine eventuelle Hilfe zur Indikationsstellung fur eine Systemtherapie [32,40,43], da ein Befall der axill~iren Lymphknoten als wichtigster Prognosefaktor gilt [22,24,28,36,69,82,113,124]. Der Wert der Axilladissektion for das GesamtUberleben wird allerdings noch diskutiert, die dazu bekannten Daten sind begrenzt und unbefriedigend.…”
Section: Stellenwert Der Axilladissektionunclassified
“…For example, Debois and others demonstrated that patients presenting with supraclavicular metastases have a poor prognosis and that more than 50% succumb to disease within three years of diagnosis 6,13,14 . In contrast, Olivotto et al showed that a significant minority (approximately 13%) may be long-term survivors 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This classification of stage was justified by evidence suggesting that the prognosis in patients with neck disease was poor, with five-year survival rates in the order of 5–34% 2–4 . Evidence also suggested this poor prognosis to be similar to that of patients with metastases in other sites (ie bone, liver) 5 with treatment not seeming to influence survival 6 . Since limited literature exists guiding treatment for isolated ipsilateral cervical metastases, management remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the previous edition of the AJCC Manual for Staging of Cancer 4 had multiple sources of evidence 5−7 to support its decision to include supraclavicular lymph node metastases as M1 disease. The study by Kiricuta et al.…”
mentioning
confidence: 99%